Relationship of Physical Fitness with metabolic markers in basketball athletes (Research, Society and Development, 2022)
The aim of the study was to compare the physical fitness (PA) levels of adolescent basketball athletes and to correlate metabolic markers with the physical fitness of basketball players. Cardiovascular risks were assessed by measuring weight, height, waist circumference (WC), blood pressure (BP), body mass index (BMI), cortisol and C-reactive protein; in addition to physical fitness by tests of flexibility, muscular endurance, agility, speed, upper and lower limb strength and VO2MAX. For data analysis, a Pearson correlation, Student “t” test and a crosstab were performed. The results for upper limb strength PA were: Excellent for athlete adolescents (75%) and junior adolescents (14.3%). For the strength of the lower limbs they were: Excellent and Very Good for adolescent professional athletes (50% and 37.5%, respectively), and Very Good for adolescents from the base (57.1%). Furthermore, the greater the agility, the lower the strength of the lower limbs (r=-0.577, p